Digital Vlogs as Learning Narratives: A Case Study of Student Engagement in Online Learning Environments - Makhrus Ali; Ethan Tan; Ryan Teo (Yayasan Adra Karima Hubbi, 2026)
Background. Digital vlogs offer multimodal narrative spaces combining visual, auditory, and reflective elements, yet existing research has not systematically examined how vlogs function as learning narratives or their specific influence on multidimensional student engagement over time. Purpose. This qualitative case study investigated how digital vlogs operate as learning narratives and influence behavioral, emotional, and cognitive dimensions of student engagement in online learning environments, guided by the Community of Inquiry framework and narrative learning theory. Method. Eighteen undergraduate students enrolled in an online educational psychology course participated in semester-long data collection involving seven vlog submissions, three-point semi structured interviews, reflective journals, and artifact analysis. Results. Findings reveal progressive engagement development with vlog length increasing from 3.2 to 5.7 minutes, reflective depth scores rising from 2.8 to 4.3, and narrative elements increasing from 68% to 89%. Three primary themes emerged: narrative ownership (94% of participants), multimodal expression (83%), and social presence (78%). Conclusion. The study's novelty lies in demonstrating that asynchronous video narratives generate authentic social presence and in integrating narrative learning theory with the Community of Inquiry framework, providing educators with conceptual tools for designing engagement-focused online learning experiences.